Mechanical Vibration Damping and Compression Properties of a Lattice Structure - Monkova, Katarina; Vasina, Martin; Zaludek, Milan; Monka, Peter Pavol; Tkac, Jozef (Materials (Basel, Switzerland), 2021)
The development of additive technology has made it possible to produce metamaterials with a regularly recurring structure, the properties of which can be controlled, predicted, and purposefully implemented into the core of components used in various industries. Therefore, knowing the properties and behavior of these structures is a very important aspect in their application in real practice from the aspects of safety and operational reliability. This article deals with the effect of cell size and volume ratio of a body-centered cubic (BCC) lattice structure made from Acrylonitrile Butadiene Styrene (ABS) plastic on mechanical vibration damping and compression properties. The samples were produced in three sizes of a basic cell and three volume ratios by the fused deposition modeling (FDM) technique. Vibration damping properties of the tested 3D-printed ABS samples were investigated under harmonic excitation at three employed inertial masses. The metamaterial behavior and response under compressive loading were studied under a uniaxial full range (up to failure) quasi-static compression test. Based on the experimental data, a correlation between the investigated ABS samples' stiffness evaluated through both compressive stress and mechanical vibration damping can be found.
Keywords: mechanical vibration; compression behavior; excitation frequency; displacement transmissibility; Acrylonitrile Butadiene Styrene; 3D printing